Polarimetric radar interferometry in the presence of differential Faraday rotation. (1st April 2022) - Gilman, Mikhail; Tsynkov, Semyon
Abstract: Faraday rotation (FR) affects the low-frequency transionospheric radar by creating cross-talk between polarizations. The baseline part of FR can be compensated for by applying an appropriate linear transformation—rotation with a known FR angle. Yet the differential Faraday rotation (dFR), which is a frequency-dependent part of FR, persists and introduces distortions into the observations. We build a simplified model with two polarimetric scattering channels that allows us to evaluate the effect of dFR on the accuracy of PolInSAR reconstruction. We also assess the severity of distortions due to dFR for the future BIOMASS mission and several other spaceborne radar systems.